Assessment of Teaching Strategies, Utilization of Student Worksheets, and Student Engagement in Science Education - Fadillah, Muhammad Aizri; Usmeldi, Usmeldi; Festiyed, Festiyed; Lufri, Lufri; Mawardi, Mawardi (International Journal of Education, Information Technology, and Others, 2025)
Science education is essential for developing students’ ability to understand and apply scientific concepts in real-world contexts. However, existing studies often examine teaching strategies, worksheet usage, and engagement in isolation, leaving a gap in understanding their interconnected dynamics. This study examines the relationships between teaching strategies, student worksheets, and student engagement in science education. Conducted in junior high schools in North Sumatra, Indonesia, with 51 participants aged 13–15, the research employed a survey method analyzed via multiple regression. Results show a strong link between teaching strategies and worksheet use. Contextualized teaching encourages worksheets for analyzing experimental data, while project-based approaches promote their use in collaborative tasks. Worksheets significantly enhance engagement by fostering participation, confidence, and problem-solving. They provide structure, deepen understanding, and strengthen critical thinking and collaboration. Aligning teaching strategies with well-designed worksheets creates a dynamic learning environment, improving engagement and outcomes. Educators and policymakers should prioritize integrative approaches and effective teaching aids to optimize learning.